Profitability of Swedish Red-and-White × Holstein crossbred cows compared with purebred Holstein cows - D.F. Pipino; N. López-Villalobos; R.E. Hickson; V.E. Cabrera; M. Balzarini; M. Piccardi (Journal of Dairy Science)
ABSTRACT: An economic analysis was performed using a bioeconomic simulation model based on production, reproduction, and longevity indicators to compare the profitability (net income per cow) of Swedish Red-and-White × Holstein (S×H) cows and pure Holstein (HOL) cows in commercial dairy farms of the center-south of Córdoba province, Argentina. The reproductive events analyzed in the model were pregnancy, calving, and abortion. The longevity events were culling, sale, and death. The lactation curve for each cow was modeled with a lactation function. Estimations were made for the first, second, and third and later lactations. Income sources were from milk, culled cows, and calves. Costs were from feeding, reproductive program, and replacement heifers. The reproductive cost of a HOL cow per year was greater than that of a S×H crossbred cow (US$6.30). The replacement costs were also higher in pure HOL cows than in S×H cows (US$67.80). The revenues from the sale of calves (US$12.10) and milk production minus the feed cost (US$8.20) were greater for S×H cows than HOL cows. Hence, the S×H cows generated a greater total profit (US$94.40) per cow per year than HOL cows. The present results show that in the studied production systems, S×H crossbred cows are more profitable than HOL cows.